Cocoa Production in Ghana (1879-1976) - Kuusaana, Mariama Marciana; Adu-Gyamfi, Samuel; Darkwa, Benjamin Dompreh (Studia Historiae Oeconomicae, 2021)
Cocoa production has been a major source of income and revenue to many citizens and the governor of Ghana respectively through time. Historically, although attributed to Tetteh Quarshie, records have shown that prior to Tetteh Quarshie’s achievement, the Dutch and Basel Missionaries had experimented with the crop in the Gold Coast. Since its introduction in the country, cocoa production has expanded and spread across all the regions in Ghana. The production of cocoa has affected every facet of development in the country since its inception and has once led Ghana to be world’s major exporter of the beans. Cocoa production in Ghana has gone beyond its agricultural and economic significance with its impacts felt across socio-cultural, religious and political life of Ghanaians. That notwithstanding, scholars have made partial effort at addressing the impact of cocoa production among Ghanaians between 1879 and 1976. Using a qualitative approach rooted in both primary and secondary sources, the current study sought to address the gap aforementioned by tracing the relationship between cocoa production and economics, politics and social-religious practices among Ghanaian between 1879 and 1976. Findings from the discourse revealed that though an agricultural product, cocoa can no longer be said to belong to that sphere alone. The product and its associated gains have permeated the entire life of Ghanaians since its inception.